Albert Watkins and Howard Watkins Family Genealogy Trip to Tennessee - Watkins, Howard::::::::: (1986)
Gravesites of William A. Watkins (11/15/1865-1/25/1941) AND Mary E. Watkins (1/15/1967-1/26/1953)